Philosophy of action and creativity in Wilhelm Feldman’s historical syntheses - Bohun, Michał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Wilhelm Feldman – a writer, publicist, literary critic, activist and political thinker, legendary editor of “Krytyka” in Kraków – was also an initiator and participant in many Young Poland discussions. The article is an attempt to reconstruct the basic ideas and intuitions present in Feldman’s major historical works and minor sketches. The author argues that they are philosophical in nature and form a coherent position. His philosophy combines romantic inspirations with the positivist programme of organic work and with elements of independence socialism, constituting an important element in the philosophical thought of Polish modernism in Galicia.

Wilhelm Feldman – pisarz, publicysta, krytyk literacki, działacz i myśliciel polityczny, legendarny redaktor krakowskiej „Krytyki”, był inicjatorem i uczestnikiem wielu młodopolskich dyskusji. Artykuł jest próbą rekonstrukcji podstawowych idei i intuicji obecnych w głównych pracach historycznych Feldmana i pomniejszych szkicach. Autor twierdzi, że mają one charakter filozoficzny i tworzą spójne stanowisko. Jego filozofia łączy inspiracje romantyczne z pozytywistycznym programem pracy u podstaw oraz z elementami socjalizmu niepodległościowego, stanowiąc ważny element myśli filozoficznej polskiego modernizmu w Galicji.
Keywords: Wilhelm Feldman; romanticism; modernism; socialism; philosophy of culture; romantyzm; modernizm; socjalizm; filozofia kultury